2017
DOI: 10.1002/jbmr.3327
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Osteocyte Perilacunar and Canalicular Remodeling in the Hyp Mouse Model of X-Linked Hypophosphatemia

Abstract: Osteocytes remodel their surrounding perilacunar matrix and canalicular network to maintain skeletal homeostasis. Perilacunar/canalicular remodeling is also thought to play a role in determining bone quality. X-linked hypophosphatemia (XLH) is characterized by elevated serum fibroblast growth factor 23 (FGF23) levels, resulting in hypophosphatemia and decreased production of 1,25 dihydroxyvitamin D (1,25D). In addition to rickets and osteomalacia, long bones from mice with XLH (Hyp) have impaired whole-bone bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 49 publications
5
48
0
Order By: Relevance
“…Even with normal renal function, elevated FGF23 is known to negatively affect bone homeostasis, as underscored by the rachitic phenotype of patients with autosomal dominant hypophosphatemia (ADHR) (21) and X-linked hypophosphatemia (XLH) (58). Recent studies demonstrated that FGF23 neutralization using anti-FGF23 antibodies in the Hyp mouse model of XLH (59) or in XLH patients (60) was able to correct serum phosphorus levels to within the normal ranges and improve bone parameters. However, with compromised renal function, use of a neutralizing FGF23 antibody in a rat model of CKD led to the deaths of the animals (61).…”
Section: Discussionmentioning
confidence: 99%
“…Even with normal renal function, elevated FGF23 is known to negatively affect bone homeostasis, as underscored by the rachitic phenotype of patients with autosomal dominant hypophosphatemia (ADHR) (21) and X-linked hypophosphatemia (XLH) (58). Recent studies demonstrated that FGF23 neutralization using anti-FGF23 antibodies in the Hyp mouse model of XLH (59) or in XLH patients (60) was able to correct serum phosphorus levels to within the normal ranges and improve bone parameters. However, with compromised renal function, use of a neutralizing FGF23 antibody in a rat model of CKD led to the deaths of the animals (61).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism, however, by which the loss of one endopeptidase, PHEX, affects other proteolytic cascades is yet to be determined. Enhanced expression of cathepsin K and MMP13 have been localized to the Hyp mouse osteocyte niche (Tokarz et al, 2018). Cathepsin K is known to cleave collagens type I and II at multiple sites along the triple helix (McKleroy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(31) Moreover, osteocyte-enriched cultures have been used to study the effects of aging on osteocytic gene expression, (32) the role of Piezo on osteocyte mechanotransduction, (33) and the dysregulation of gene expression in osteocytes in X-linked hypophosphatemia. (34) This protocol can be used with bones isolated from WT and genetically modified mice. When testing treatments in ex vivo bone organ cultures, we recommend performing dose-and time-course experiments to determine the ideal conditions for your genes/proteins of interest.…”
Section: Studies Of Osteocyte Functionmentioning
confidence: 99%
“…Similarly, Stegen and colleagues employed ex vivo osteocyte‐enriched bone cultures to study the effects of oxygen in osteocytes and identified the oxygen‐sensing Phd2 as an important regulator of sclerostin and bone mass . Moreover, osteocyte‐enriched cultures have been used to study the effects of aging on osteocytic gene expression, the role of Piezo on osteocyte mechanotransduction, and the dysregulation of gene expression in osteocytes in X‐linked hypophosphatemia …”
Section: Use Of Ex Vivo Bone Organ Cultures For the Study Of Bone Biomentioning
confidence: 99%